2017
DOI: 10.1093/jscr/rjx020
|View full text |Cite
|
Sign up to set email alerts
|

Distant melanoma causing small bowel obstruction

Abstract: Small bowel obstructions (SBOs) are common. Adhesions make up the majority of cases at 84.9%, followed by abdominal herniae and malignancies. A 71-year-old female presented with total constipation, abdominal distension, on a background of resected cutaneous melanoma nine years prior. A CT-scan showed small bowel intussusception and disseminated mucosal-enhancing lesions consistent with metastases. She was brought to the operating theatre where six areas of intussusception were identified and manually reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…A systematic review and meta-analysis by Hong et al showed that a metastatic carcinoma acted as a culprit in the majority of intussusception cases [9]. Known for its high metastatic potential, malignant melanoma has the tendency to metastasize to the gastrointestinal tract as the third most common site, with the small intestine commonly affected which is largely attributed to its rich blood supply [10][11][12]. Despite this, metastatic melanoma causing small bowel obstruction is relatively rare [3].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Hong et al showed that a metastatic carcinoma acted as a culprit in the majority of intussusception cases [9]. Known for its high metastatic potential, malignant melanoma has the tendency to metastasize to the gastrointestinal tract as the third most common site, with the small intestine commonly affected which is largely attributed to its rich blood supply [10][11][12]. Despite this, metastatic melanoma causing small bowel obstruction is relatively rare [3].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases are due to metastasis from a primary cutaneous lesion, and few reports of primary melanoma of the small bowel exist in the literature. An autopsy study found that 60% of all patients with melanoma had intestinal metastasis, with the small intestine being involved in 50% of cases, the colon in 31%, and the ano-rectum in 25% [6]. Hintze et al concluded that melanoma is the “most common extra-intestinal malignancy to metastasize to the [GI tract], and metastases can occur many years later” [6].…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy study found that 60% of all patients with melanoma had intestinal metastasis, with the small intestine being involved in 50% of cases, the colon in 31%, and the ano-rectum in 25% [6]. Hintze et al concluded that melanoma is the “most common extra-intestinal malignancy to metastasize to the [GI tract], and metastases can occur many years later” [6]. The higher incidence of metastasis to the small bowel may be due to its rich blood supply [7].…”
Section: Discussionmentioning
confidence: 99%
“…Metastases from an unknown primary to the small bowel can well be a cause of obstruction and manifest in an emergency setting [ 98 , 99 ]: a description of bifocal metastases of melanoma treated through partial resection of the jejunum and distal ileum with termino-terminal anastomosis have been described.…”
Section: Main Findings Of the Literature (Review) Questmentioning
confidence: 99%